Pengaruh Pengawasan Terhadap Disiplin Kerja Pegawai Negeri Sipil Di Sekretariat Daerah Kabupaten Kepulauan Sula - Umamit, Sulma; Mandey, Jantje; Rares, Joyce Jacinta (Sam Ratulangi University, 2016)
ABSTRACT : The research was conducted on the basis of initial observations that civilservants in performing basic tasks and functions indicated less comply with the applicable rules,especially rules regarding discipline in performing the task. Thus, the study aims to